EMOTION AND HEALTH. TRENDS IN BASIC AND APPLIED PSYCHOLOGY. PRESENTATION OF SPECIAL ISSUE - Martínez Sánchez, Francisco; Fernández Castro, Jordi (Anales de Psicología / Annals of Psychology)
This paper reviews the role of human emotions on health and illness. Interest in psychological factors of illness is baseson epidemiological data. The authors examine Grave’s disease as an example of these relationships. Data supporting the evidence of the influencies of emotions on the process of becoming ill are also reviewed. Finally, the contributions of the different authors tho this journal special issue are examined.